Preparation of Metal-Free Nitrogen-Doped Carbon Material and Its Catalytic Performance - Xuan Wang; Lei Yang; Ke-ying Cai; Ying Mei Zhou; Peng Wang; Ming Song (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Nitrogen-doped carbon materials (NCMs) were prepared via hydrothermal treatment together with pyrolysis under nitrogen atmosphere by using melamine as nitrogen source and sucrose as carbon source. The NCMs were characterized by X-ray diffraction (XRD), laser Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The results showed that nitrogen species were successfully doped into NCMs in the formation of pyridinic N, pyrrolic N, graphitic N, and oxidized N. With the temperature of pyrolysis increasing, the total amount of nitrogen species decreased, while the proportion of graphitic N increased. The catalytic performance was investigated by the reduction of p-nitrophenol with excessive KBH4 at 30 ℃. The reaction rate constant can reach 1.06 min-1 for NCM-800. The NCM-800 has good stability, which can be used for 8 cycles without obvious deactivation.